Mukalma Bainal Mazahib ki Jihat: Mustafavi Manhaj Arab ke Yahud o Nasara se Tahamul ki Roshni Main: مکالمہ بین المذاہب کی جہات: مصطفوی منہج (عرب کے یہود و نصاریٰ سے تعامل کی روشنی میں) - Brohi, Dr. Abdul Fareed; Rehman, Dr. Qari Zia ur; Rajpar, Muhammad Aslam (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
Islam is the religion of peace and coherence revealed to the Prophet Muhammad (peace be upon him) as a true guidance and mercy for the mankind. As the Prophet preached the message of Islam in Arabia, which later on spread in almost all the continents, Muslims interacted with the adherents of different religions, cultures, civilizations, ethnicities and creeds. When the Prophet migrated to Madina; he had interacted there with the Jews of Madinah and later on with the Christians of Arabia. These encounters and models include the migration, battles, treaties and dialogues within and without. In human history, the cultures and civilizations are compelled to relate to one another on a continuous and constant basis. Although the move towards inter-religious dialogue was first started within a Protestant branch of the Christian church, and the idea of interfaith dialogue is relatively modern but some of its instances could be traced back to the history of Islam as well. The main theme of this study and research will focus on the Prophetic approach and methodology towards dialogue. The researcher will try to seek the answers of the issues of today’s world which are being faced by the world in general and the Muslim Ummah in particular related to interfaith dialogue. The study will sort out the guidelines which could be found in the Life of the Prophet and the attitude and Hikmah (wisdom) of the Prophet towards dialogue seeking a Prophetic approach for the contemporary phenomenon of cultural and civilisational pluralism.